Rayleigh-based raman fiber laser with passive erbium-doped fiber for secondary pumping effect in remote l-band erbium-doped fiber amplifier - Abu Bakar, M.H.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This work focuses on a secondary pumping scheme for remote L-band erbium-doped fiber amplifier (R-EDFA) generated by integrating Rayleigh-based ultralong Raman fiber laser (ULRFL) with a section of passive erbium-doped fiber (EDF). A selective wavelength reflector combined with Rayleigh feedback in the transmission span forms the ULRFL cavity while the passive EDF deployed at the end of the span converts the ULRFL into a secondary C-band pump. Optimum ULRFL wavelength is determined by tuning the selective wavelength reflector across the C-band region. Combination of R-EDFA gain, Raman amplification, and passive EDF provides gain improvement as high as 15.5 dB over conventionally pumped R-EDFA with minimal optical signal-to-noise ratio penalty.